Interest Rate Policy in Central and Eastern Europe : The Influence of Monetary Overhangs and Weak Enterprise Discipline - Schadler, Susan (IMF Working Papers; Working Paper ;, 1992)
Interest rate policy in the newly reforming Central and Eastern European countries has generally been geared toward establishing positive real interest rates and defending the exchange rate. The principal instrument for this task has been administrative increases in controlled interest rates. This paper examines the effect of these adjustments on inflation, the real interest rate and the exchange rate. It points out the risk that when financial discipline over enterprises is weak raising nominal interest rates may do little more than raise credit growth, the rate of depreciation and ultimately inflation. Simulations attempt to shed light on the importance of these linkages.